Ethnopsychological and phenomenological explication of traumatic experience in Ukrainian culture through the works of Hnat Khotkevych - YARMOLITSKA, Nataliia; YEVDOKYMOVA, Liudmyla; TOVMASH, Dmytro (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. This article is dedicated to the analysis of the works of Ukrainian writer Hnat Khotkevych through the lenses of ethnopsychology and phenomenology as methods for exploring the collective traumatic experience of Ukrainian culture. Khotkevych’s literary texts are examined as carriers of collective trauma, represented in artistic form. Special attention is paid to the analysis of literary images and themes that reflect such traumatic conditions as alienation, repression, spiritual duality, the destruction of traditional lifestyles, individual and collective pain, national oppression, and the tragedies of historical memory. The study investigates how the intentionality of Khotkevych’s consciousness – directed toward experiencing national identity – is embodied in the linguistic imagery and artistic structure of his works. Methods. An interdisciplinary approach is applied, combining ethnopsychological analysis, phenomenological reduction, historical-cultural hermeneutics, and textual interpretation. Results. It has been established that Khotkevych’s work represents a form of national memory, wherein individual experiences are transformed into a cultural, archetypal model of trauma (collective, historical, and ethnic). His texts function not only as aesthetic objects but also as phenomena of collective memory, reflecting deep layers of the Ukrainian people’s ethnopsychic consciousness. It is demonstrated that by synthesizing folkloric, historical, and personal motifs, Khotkevych constructed an artistic paradigm in which national memory emerges as a deeply rooted source of self-understanding and spiritual resistance. In this sense, his creative legacy fulfills a function of cultural therapy, preserving the integrity of identity amid historical catastrophes. The study outlines new approaches to literary text analysis as a space of traumatic experience, underscoring the need for further exploration of such practices within contemporary humanities. Conclusions. Hnat Khotkevych not only depicted the historical wounds of the Ukrainian people but also transformed them into symbolic images that contributed to the consolidation of the national "self" and the preservation of identity.